Amodal Completion of a Target Template Enhances Attentional Guidance in Visual Search. (August 2018) - Chen, Siyi; Schnabl, Lucas; Müller, Hermann J.; Conci, Markus
When searching for a target object in cluttered environments, our visual system appears to complete missing parts of occluded objects—a mechanism known as "amodal completion." This study investigated how different variants of completion influence visual search for an occluded target object. In two experiments, participants searched for a target among distractors in displays that either presented composite objects (notched shapes abutting an occluding square) or corresponding simple objects. The results showed enhanced search performance when composite objects were interpreted in terms of a globally completed whole. This search benefit for global completions was found to be dependent on the availability of a coherent, informative simple-object context. Overall, these findings suggest that attentional guidance in visual search may be based on a target "template" that represents a globally completed image of the occluded (target) object in accordance with prior experience.